Mechanical Properties of Hybrid and Polymer Matrix Composites That Used To Manufacture Partial Foot Prosthetic - Hussain, Hassanein Salih; Takhakh, Ayad Murad (Al-Nahrain Journal for Engineering Sciences, 2017)
In this study, an experimental comparison has been made between the traditional plastic materials (Polypropylene and Polyethylene) and selected composite materials (Perlon-Carbon-Perlon and Hybrid Carbon fiber-Glass fiber) to manufacture a long life Partial Foot Prosthesis. To improve the mechanical properties, increase the lifetime of the prosthesis, and reduce the cost to the patient, two types of composite materials were used and compared with plastic materials. Samples were manufactured and tested with different test methods (Tensile, flexural, and fatigue test). All tests were performed at room temperature.The results showed that the composite materials achieve a large increment in mechanical properties such as (?y, ?ult, E, ?b, and Ef) whichwere increased to a percentage of (200% - 261%),(330% - 243%), (295% - 203%), (276% - 270%),and (413% - 301%) in Perlon-Carbon-Perlonlamination as compared with Polypropylene andPolyethylene respectively. However theincreasing percentage in Hybrid Carbon fiber-Glass fiber was (353% - 270%), (470% - 347%),(388% - 267%), (203% - 199%), and (244% -178%) as compared with Polypropylene andPolyethylene. At the same time, the fatigue lifewas sharply increased in both of the Perlon-Carbon-Perlon and Hybrid Carbon fiber-Glassfiber.